MODESTY IN DISCOURSE ANALYSIS. A COMPARATIVE STUDY OF ENGLISH AND UZBEK LANGUAGES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This study examines the manifestation of modesty in discourse within English and Uzbek languages, highlighting its linguistic, sociolinguistic, and pragmatic dimensions. Modesty is defined and contextualized as a politeness strategy that helps maintain harmonious communication by discouraging self-praise.